Determinants Of Microfinance Factors Affecting Women's Empowerment: Evidence From Egypt - Ali Hamid Irhoumah; Abdullah Moh'd Ayedh; Abdelghani Echchabi (Shaheed Benazir Bhutto Women University Peshawar, 2024)
Indexed by WOS/SCOPUS